Cajal’s organization of neuronal nucleus revisited - Lafarga, Miguel; Berciano, María T.; Narcís, J. Oriol; Baltanás, Fernando C.; Tapia, Olga (Frontiers in Neuroanatomy, 2025)
In 1906, Cajal was awarded the Nobel Prize in Physiology or Medicine for his pioneering studies on the structure and organization of nerve centers. Notably, in 1910, Cajal published a seminal work in which he described the essential components of the neuronal nucleus, primarily using his reduced silver nitrate procedure. Using modern microscopy techniques, we have identified the current equivalents of the structures originally described by Cajal. These include the “fibrillar center–dense fibrillar component units” of the nucleolus, “nuclear speckles,” “transcription factories,” and “the Cajal body.” Importantly, these structures represent key nuclear compartments involved in the transcription of rDNA and protein-coding genes, pre-rRNA and pre-mRNA processing and spatial genome organization. Most of the nuclear components described by Cajal are now recognized as dynamic “nuclear condensates” assembled through liquid–liquid phase separation mechanisms that depend on various categories of RNA and RNA-binding proteins.